ANALYZING THE RHYTHM OF NARRATION IN THE MAIN INTRODUCTION OF ’MEM AND ZIN’ BY AHMAD KHANI ACCORDING TO GÉRARD GENETTE’S CONCEPT OF TIME - Yousef, Dilman; Omar, Payman (Humanities Journal of University of Zakho, 2026)
This study, titled "Analyzing the Rhythm of Narration in the Main Introduction of ’Mem and Zin’ by Ahmad Khani According to Gérard Genette’s Concept of Time," is a comprehensive analysis of the narrative rhythm in the main introduction of Ahmad Khani’s masterpiece "Mem and Zin," relying on Gérard Genette’s theory of "time." The main objective is to identify the narrative rhythms (fast and slow) in the introduction of "Mem and Zin," especially the dominant rhythm that Khani used to build the foundation of the epic. The study investigates the factors and effects of using these rhythms to convey profound messages. The descriptive-analytical method has been used, and the analysis will be conducted according to Gérard Genette’s theory of "time." The scope of the study is limited to the main introduction of Khani’s "Mem and Zin," with its introductory poems taken as the primary material for practical application. The study attempts to answer several hypotheses, such as: How and where does the main introduction of the epic begin and end? Which technique did Khani use more frequently? Did it lead to the identification of a specific type of rhythm ("fast or slow") as the main rhythm in the main introduction? The results obtained in this study are: In the main introduction, which begins with "In the name of God" and extends to "The Introduction of Mem," Khani constructs the world of the story in a descriptive and lengthy manner. Khani utilized both fast and slow rhythms; especially the use of slow rhythm and the technique of descriptive pauses. This slow rhythm and descriptive style, mean that, the dominant rhythm is the slow rhythm. Builds the story’s world, introduces characters and relationships, and prepares the reader for major and future events.